ANALISA NPSH KERUSAKAN IMPELLER POMPA CETRIFUGAL CAIRAN CH3OH - Rosmiati Rosmiati; Tayeb Ibrahim; Masykur Masykur (universitas teuku umar, 2019)
Liquid behavior is always influenced by the environment in the form of temperature and pressure (thermodynamics). This temperature and pressure affect the nature of the change in liquid phase into a mixture of water and steam or vice versa. Pumps that function to drain liquid also have temperature and pressure. If the pressure drops and the temperature stays or rises at the pump, the liquid phase changes to a liquid and vapor mixture phase. This phase change in the pump (suction side) is called the phenomenon capitation. Capitation in the pump will cause erosion of the impellers parts, resulting in decreased performance. This study analyzes the erosion of the casing and impeller at the 040-G01S pump of PT. KMI from the point of phenomenon of capitation. The phenomenon of capitation in pump suction empirically can be known if the required NPSHa value is less or equal to the available NPSHr value or NPSHa ≦ NPSHr. The NPSHa value is affected by the suction pump installation configuration. To find out the cause of erosion on the casing and impeller, it is necessary to calculate the NPSH (Net Positive Section Head) required and those available (manufacturers). The results of this study NPSHa value = 4.75 m and NPSHr value = 5 m) or NPSHa ≦ NPSHr at tank level <45%. So it is necessary to modify the installation of the pump suction side piping.